Human GBP1 does not localize to pathogen vacuoles but restricts Toxoplasma gondii. (10th March 2016) - Johnston, Ashleigh C.; Piro, Anthony; Clough, Barbara; Siew, Malvin; Virreira Winter, Sebastian; Coers, Jörn; Frickel, Eva‐Maria
Summary: Guanylate binding proteins (GBPs) are a family of large interferon‐inducible GTPases that are transcriptionally upregulated upon infection with intracellular pathogens. Murine GBPs (mGBPs) including mGBP1 and 2 localize to and disrupt pathogen‐containing vacuoles (PVs) resulting in the cell‐autonomous clearing or innate immune detection of PV‐resident pathogens. Human GBPs (hGBPs) are known to exert antiviral host defense and activate the NLRP3 inflammasome, but it is unclear whether hGBPs can directly recognize and control intravacuolar pathogens. Here, we report that endogenous or ectopically expressed hGBP1 fails to associate with PVs formed in human cells by the bacterial pathogens Chlamydia trachomatis or Salmonella typhimurium or the protozoan pathogen Toxoplasma gondii . While we find that hGBP1 expression has no discernible effect on intracellular replication of C . trachomatis and S . typhimurium, we observed enhanced early Toxoplasma replication in CRISPR hGBP1‐deleted human epithelial cells. We thus identified a novel role for hGBP1 in cell‐autonomous immunity that is independent of PV translocation, as observed for mGBPs. This study highlights fundamental differences between human and murine GBPs and underlines the need to study the functions of GBPs at cellular locations away from PVs.